2021
DOI: 10.21037/sci-2020-048
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapeutic combination of mesenchymal stem cells and stigmasterol to attenuate osteoarthritis in rodent model system— a proof of concept study

Abstract: Mesenchymal stem cells (MSCs) have gained wide therapeutic acceptance in regenerative medicine due to their potential in repair process in restoring the damaged tissues and controlling inflammation. In the present study, we report for the first time the beneficial effects of combining placentalderived MSCs (hPMSCs) with stigmasterol-a plant-derived sterol to accelerate cartilage repair and regeneration in a monosodium-iodoacetate (MIA) induced osteoarthritis (OA) rat model. Control animals (Group I) received n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In order to develop a novel therapeutic approach to alleviate OA, Sampath et al [ 45 ] conducted an in vivo study to examine the effect of the combination of mesenchymal stem cells (MSCs) and stigmasterol in a monosodium-iodoacetate (MIA)-induced experimental OA in rats. The results demonstrated that the combination treatment led to consistent regeneration/repair of eroded cartilage in the femoral condyles and also in the trochlear groove, highlighting the importance of combined treatment over individual therapies in rats with OA.…”
Section: Anti-osteoarthritis Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop a novel therapeutic approach to alleviate OA, Sampath et al [ 45 ] conducted an in vivo study to examine the effect of the combination of mesenchymal stem cells (MSCs) and stigmasterol in a monosodium-iodoacetate (MIA)-induced experimental OA in rats. The results demonstrated that the combination treatment led to consistent regeneration/repair of eroded cartilage in the femoral condyles and also in the trochlear groove, highlighting the importance of combined treatment over individual therapies in rats with OA.…”
Section: Anti-osteoarthritis Effectsmentioning
confidence: 99%
“…Previous studies found that stigmasterol relieved cartilage degradation in rodent models of osteoarthritis [ 44 ]. When combined with mesenchymal stem cell secretome, stigmasterol reduces inflammation and leads to constant regeneration/repair of eroded cartilage [ 45 , 46 ]. This phytosterol could be considered in new therapeutic designs since it has anti-inflammatory and analgesic properties that can overcome osteoarthritis effects [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, 8 more animals were included in this study and were subjected to HBO treatment during 14 days after OA induction. Animals from this group were sacrificed after 28 days of OA induction (HBO+ADS 28day group) in order to compare cartilage damage to rats from HBO+ADS 21day group [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies postulated that higher efficacy with MSCs can be achieved with the infusion of stem cells before disease onset or during the early phase of the disease. Recently, Sampath et al [ 54 ] reported a novel therapeutic combination of placental-derived MSCs (hPMSCs) with stigmasterol, a plant-derived sterol in the monosodium-iodoacetate osteoarthritis (OA) rat model. The authors found beneficial effects on intra-articular administration of hPMSCs with stigmasterol and demonstrated accelerated cartilage repair and regeneration using computerised tomography (micro-CT) and histopathology.…”
Section: Preclinical Animal Models Of Autoimmune Diseasesmentioning
confidence: 99%
“…The authors found beneficial effects on intra-articular administration of hPMSCs with stigmasterol and demonstrated accelerated cartilage repair and regeneration using computerised tomography (micro-CT) and histopathology. This cellular therapy attenuated osteoarthritis lesions with concomitant cartilage repair and regeneration [ 54 ].…”
Section: Preclinical Animal Models Of Autoimmune Diseasesmentioning
confidence: 99%